Enhanced Performance of Edge-Plane Pyrolytic Graphite (EPPG) Electrodes over Glassy Carbon (GC) Electrodes in the Presence of Surfactants: Application to the Stripping Voltammetry of Copper - Shishmarev, D; Rees, N; Compton, R (2010)
The voltammetric performance of glassy carbon (GC) and edge-plane pyrolytic graphite (EPPG) electrodes was investigated for the oxidation of potassium ferrocyanide in aqueous solution both with and without the addition of surfactant (sodium dodecyl sulfate and Triton X-100). The heterogeneous electron transfer kinetics were determined for all cases, and it was found that the GC electrode surface was far more sensitive to the presence of surfactant than the more hydrophilic EPPG surface. This result was then applied to the electroanalysis of copper via adsorptive stripping voltammetry in the presence of Triton X-100 and it was observed that the EPPG electrode response was unaffected by up to 100 mM of surfactant, whilst the voltammetry on the GC electrode was significantly affected by only 10 mM. © 2010 Wiley-VCH Verlag GmbHandCo. KGaA, Weinheim.